ANALISIS PEMBERIAN BENEFIT, MOTIVASI, DAN KOMITMEN ORGANISASIONAL APARATUR SIPIL NEGARA (ASN) - Nur Wening; Gunawan Purnomo (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2019)
The aim of this research is analyzing of benefit, motivation, and apparatus organizational commitment. This research is typically of quantitative discriptivemethod research. The respondents in this research are civil servants the number of respondents are 31 (thirty one) people. The result shows that the giving of benefit, motivation, and civil servant organizational commitment is already well implemented. The giving of benefit variable gives the highest mark on work performance dimension and lowest mark on professional scarcity, while motivation variable has the highest mark on social needs dimension and the lowest mark on prestige dimension, and civil servant organizational commitment variable gives the highest mark on affective commitment dimension and the lowest mark is on continuation commitment dimension.